Comparison of intra-cuff lidocaine vs alkalinized lidocaine effects for prevention of post-operative sore throat - Hassan, Sarosh Ul; Nighat Abbas; Ali Asghar; Sabahat Tariq; Nadeem Naqvi; Rafique, Muhammad (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effect of intra-cuff lidocaine versus alkalinized lidocaine in the prevention of post-operative sore throat. Method: The cross-sectional study was conducted from June 15 to July 15, 2019, at the Department of Anaesthesiology, Liaquat National Hospital and Medical College, Karachi, and comprised patients of either gender aged 15-50 years classified as American Society of Anaesthesiologist class 1-2 and going under general anaesthesia with endotracheal intubation expected to last more than one hour. The patients were randomised into Group L and Group LA. General anaesthesia was given using induction dose of propofol 2-3mg/kg, nalbuphine 0.1mg/kg and atracurium 0.5mg/kg and female patients were intubated with 7.0mm size endotracheal tube and males patients with 8.0mm. All intubations were performed by an anaesthesiologist with minimum of two-year experience. The endotracheal tube cuff was inflated by using plain lidocaine 2% in group L and 2% lidocaine with 8.4% sodium bicarbonate in LA group till the air leak diminished. Post-surgery, the patients were assessed on extubation for any emergence phenomenon and were re-assessed at 1st, 6th, 12th and 24th hour. The assessment was done by the on-call anaesthesiology resident who was blinded to the study group. Data was collected using a proforma. The analysis was done using software IBM SPSS Statistics 23.0. Chi-Square Test was applied to analyse the data. Results: Of the 58 patients, 33(56.9%) were male and 25(43.1%) were female. There were 26(44.8%) patients aged 25-36 years, while 12(20.7%) each were aged 36-45 years and 46-55 years. There were 29(50%) patients in each of the 2 groups. After 24 hours, 75.9% patients in Group L did not complain of any pain, while in group LA the corresponding number was 96.6%. Both in terms of cough and hoarseness at 24 hours, 96.6% patients in Group L did not have complaints, while in Group LA there were no such complaints. In Group L, heart rate 60-80 was noted in 20(69%) patients and 81-100 in 9(31%). In Group LA, the corresponding values were 17(58.6%) and 12(41.4%). Conclusion: Alkalinized lidocaine was found to be highly effective in preventing post-operative throat complications compared to lidocaine. Key Words: Alkalanized lidocaine, Hoarseness, Intra-cuff lidocaine, Sore throat.